A massive immature mediastinal teratoma treated with chemotherapy and surgical resection: a case report - Parviz Mardani; Hooman Kamran; Rezvan Ghaderpanah; Bita Geramizadeh; Damoun Fouladi; Reza Shahriarirad; Armin Amirian (Journal of Cardiothoracic Surgery, 2023)
Abstract Background Teratoma is a type of germ cell tumor consisting of one or multiple tissues derived from germinal layers. The location and size of the tumor can cause various presentations. Here we report one of the largest ever cases of immature cystic teratoma. Case Presentation In this report, we presented a 24-year-old patient with dyspnea, chest pain, nausea, and anorexia. A computed tomography scan revealed a giant, right-sided mass measuring about 190 × 150 × 140 mm. Chemotherapy was initiated for the patient, followed by thoracotomy. Histopathological evaluation revealed the nature of the mass to be an immature mediastinal teratoma. Conclusion the incidence of immature mediastinal teratoma is uncommon, and due to its rarity, the diagnosis needs more profound evaluation studies such as radiological and pathological assessments. Immature teratomas are optimally treated by a combination of chemotherapy and complete resection.